Sharia Business Ethics in Fuel Oil Industry - Dharma Albertd Tarigan; Pauzi Muhammad (Journal of Social, Humanity, and Education, 2026)
Purpose: This study aims to explore the application of Sharia business ethics in the fuel oil industry, focusing on its principles derived from the Al-Qur'an and Hadith, which guide business conduct and decision making. Fuel oil is a critical commodity that plays a significant role in the modern economy and societal livelihoods. Research Methodology: This study uses a normative legal research approach, utilizing case studies of legal behaviors, including reviews of relevant laws and regulations in the fuel oil industry. Results: The study found that fuel oil has long been beneficial to society, with public fuel filling stations providing easy access to the community. However, price determination errors can have long-term negative consequences. Sharia business ethics in the fuel oil industry emphasize honesty, trust, tolerance, and the fulfillment of agreements, ensuring that businesses are free from practices such as fraud (ghurur), gambling (maysir), usury (riba), bribery (riswah), and haram products. Conclusions: Sharia business ethics provide a comprehensive framework for conducting business in the fuel oil sector, promoting fairness, transparency, and social responsibility. Limitations: This study is limited to normative legal research and does not explore empirical data or case studies on business performance in the fuel oil sector. Contributions: This research contributes to understanding the importance of applying Sharia principles in the fuel oil industry, offering a moral framework for ethical business practices that benefit society and the environment.